IMMIGRATION MOVIES IN TURKEY: HOW ECONOMIC CHANGES AFFECT TURKISH CINEMA IN 1960S - Gökhan Uğur (European Scientific Journal, ESJ, 2014)
The essence of this study is defined by the Marxist concept of infrastructure and superstructure. In 1950, Adnan Menderes, the leader of Demokrat Parti (Democratic Party) won the presidential election in a landslide victory. Then, he implemented liberal economy which caused fundamental changes in the country. The changes in economic base affected the superstructure. New economic conditions forced people to move other places, especially to larger cities. Farmers became factory workers. Meanwhile, the role of women in the society was changed, since they were also integrated into the production process. Therefore, the movies dealing with the problems of immigrants emerged as a result of the new economic system. Gurbet Kuşları (1964), directed by Halit Refiğ, is the first movie which analyzes the results of these economic changes.